2007
DOI: 10.1021/jm070391t
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Mycobacterium tuberculosis, Mycobacterium bovis, and Mycobacterium avium by Novel Dideoxy Nucleosides

Abstract: The prevalence of tuberculosis (TB) and mutidrug-resistant tuberculosis (MDR-TB) has been increasing, leading to serious infections, high mortality, and a global health threat. Here, we report the identification of a novel class of dideoxy nucleosides as potent and selective inhibitors of Mycobacterium bovis, Mycobacterium tuberculosis, and drug-resistant Mycobacterium tuberculosis. A series of 5-acetylenic derivatives of 2',3'-dideoxyuridine (3-8) and 3'-fluoro-2',3'-dideoxyuridine (22-27) were synthesized an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 38 publications
(80 reference statements)
2
42
0
Order By: Relevance
“…However, recent reports on potent and selective antimycobacterial activities for pyrimidine dideoxynucleosides featuring 5-alkynyl substituents [51] and nucleoside bisubstrate analogs [52] are encouraging and seem to suggest that further finetuning of the physicochemical properties may one day afford TMPK inhibitors with the expected antimycobacterial activity. …”
Section: Resultsmentioning
confidence: 99%
“…However, recent reports on potent and selective antimycobacterial activities for pyrimidine dideoxynucleosides featuring 5-alkynyl substituents [51] and nucleoside bisubstrate analogs [52] are encouraging and seem to suggest that further finetuning of the physicochemical properties may one day afford TMPK inhibitors with the expected antimycobacterial activity. …”
Section: Resultsmentioning
confidence: 99%
“…In particular, many publications relate to the search for novel and efficient antimycobacterial agents [11][12][13][14][15][16] and this is explained by an exceptionally high surge in tubercular morbidity, approaching an epidemic scale in many countries of the world. In many examples of this kind it is necessary to include also the tendency of stimulation of the tubercular mycobacterium to active mutation contributing to rapid formation of resistance (often multiple) to known antitubercular medicines.…”
mentioning
confidence: 99%
“…During our continued search of novel anti-TB agents, we found that 5-alkynyl substituted pyrimidine nucleosides were very potent inhibitors of mycobacteria (Rai et al, 2005). We , reported that pyrimidine nucleoside analogs 1--D-2'-arabinofuranosyl-5-dodecynyluracil (10), 1-(2'-deoxy-2'-fluoro--D-ribofuranosyl)-5-dodecynyluracil (11), and 1-(2'-deoxy-2'-fluoro--D-ribofuranosyl)-5-tetradecynyluracil (12) In the same year, we (Rai et al, 2007) further reported syntheses and evaluation of a series of 5-acetylenic derivatives of 2',3-dideoxyuridine, and 3'-fluoro-2',3'-dideoxyuridine for their antimycobacterial activity against M. bovis, Mtb, and M. avium. Compound 13 (among 2',3'-dideoxyuridine series) and compound 14 (among 3'-fluoro-2',3'-dideoxyuridine series) demonstrated excellent antimycobacterial activity (MIC 1-2 g/mL) against Mtb H 37 Ra.…”
Section: Cpzen-45mentioning
confidence: 97%